Th@D5h(6)-C80: a highly symmetric fullerene cage stabilized by a single metal ion. Issue 54 (14th June 2021) - Yan, Yingjing; Morales-Martínez, Roser; Zhuang, Jiaxin; Yao, Yang-Rong; Li, Xiaomeng; Poblet, Josep M.; Rodríguez-Fortea, Antonio; Chen, Ning
Abstract : Th@ D 5h (6)-C80 is successfully synthesized and characterized. This is the first example to prove that D 5h (6)-C80 can be stabilized by the encapsulation of a single metal ion and 4-electron transfer. Abstract : A novel endohedral metallofullerene (mono-EMF), Th@ D 5h (6)-C80, has been successfully synthesized and fully characterized by mass spectrometry, single crystal X-ray diffraction, UV-vis-NIR and Raman spectroscopy and cyclic voltammetry. Single crystal XRD analysis unambiguously assigned the fullerene cage as D 5h (6)-C80, the first example in which the highly symmetric cage is stabilized by a single metal ion. The combined experimental and theoretical studies further reveal that the D 5h (6)-C80 cage, known only for its stabilization by 6-electron transfer, is stabilized by the 4-electron transfer from the encapsulated Th ion for the first time.